2022
DOI: 10.1021/acsphotonics.1c01744
|View full text |Cite
|
Sign up to set email alerts
|

Adjoint-optimized metasurfaces for compact mode-division multiplexing

Abstract: Optical fiber communications rely on multiplexing techniques that encode information onto various degrees of freedom of light to increase the transmission capacity of a fiber. However, the rising demand for larger data capacity is driving the need for a multiplexer for the spatial dimension of light. We introduce a mode-division multiplexer and demultiplexer design based on a metasurface cavity. This device performs, on a single surface, mode conversion and coupling to fibers without any additional optics. Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“… 34 While the concept has proven to be especially powerful for wavelength and polarization-multiplexing tasks, angular multiplexing, i.e., the generation of different output fields at varying input angles, appears harder to achieve: only up to four multiplexed fields could be generated upon a large angular variation of more than 60 deg 35 . Some folded multiplane designs using metasurfaces have been realized recently to increase the multiplexing capabilities of these metaholograms 36 . Yet, the advantages of using metasurfaces in this context seems limited, since three reflections are required to achieve only a three-mode sorter, which is not significantly better than what more conventional cascaded diffractive optical elements can provide 9 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 34 While the concept has proven to be especially powerful for wavelength and polarization-multiplexing tasks, angular multiplexing, i.e., the generation of different output fields at varying input angles, appears harder to achieve: only up to four multiplexed fields could be generated upon a large angular variation of more than 60 deg 35 . Some folded multiplane designs using metasurfaces have been realized recently to increase the multiplexing capabilities of these metaholograms 36 . Yet, the advantages of using metasurfaces in this context seems limited, since three reflections are required to achieve only a three-mode sorter, which is not significantly better than what more conventional cascaded diffractive optical elements can provide 9 …”
Section: Discussionmentioning
confidence: 99%
“…35 Some folded multiplane designs using metasurfaces have been realized recently to increase the multiplexing capabilities of these metaholograms. 36 Yet, the advantages of using metasurfaces in this context seems limited, since three reflections are required to achieve only a three-mode sorter, which is not significantly better than what more conventional cascaded diffractive optical elements can provide. 9…”
Section: Metahologramsmentioning
confidence: 99%
“…In contrast with the forward design approach, the inverse design could optimize the desired complex functionality by reshaping the regular meta-atoms into arbitrarily irregular topology. One of the typical inverse design approaches is adjoint-based topology optimization, which is a local gradient descent algorithm requiring only two steps of full-wave electromagnetic simulation for each iteration process . Recently, it has demonstrated great success in realizing complex functionalities of metasurfaces and meta-optics, such as meta-gratings, metalens, disordered metasurfaces, , and other freeform metasurfaces. , For example, as shown in Figure a, Sell et al demonstrated a topology-optimized large-angle deflection meta-grating with 75% absolute deflection efficiency at 1050 nm . As shown in Figure b, Sang et al comprehensively investigated the efficiency gap between the conventional high numerical aperture (NA) metalens and the theoretical limitation of vector diffraction theory .…”
Section: Intelligent Design Of Metasurfacesmentioning
confidence: 99%
“…[34]. Some folded multiplane designs using metasurfaces have been realized recently in order to increase the multiplexing capabilities of these meta-holograms [35]. Yet, the advantages of using metasurfaces in this context seems limited since 3 reflections are required to achieve only a 3-mode sorter, which is not significantly better than what more conventional cascaded diffractive optical elements can provide [9].…”
Section: Meta-hologramsmentioning
confidence: 99%